Pendugaan Stok Cumi-cumi Loligo sp. di Perairan Kabupaten Pangkajene dan Kepulauan, Sulawesi Selatan, Indonesia (Stock Assessment of Squid Loligo sp. in Pangkajene and Kepulauan Regency, South Sulawesi, Indonesia) - Susiana, Susiana; Rochmady, Rochmady (Program Studi Manajemen Sumber Daya Perairan, 2018)
The objectives of the study were to analyze the sustainable yield level and the optimum catching of the squid Loligo sp. in the waters of Pangkajene and Kepulauan Regency, South Sulawesi, Indonesia. The study was conducted from April to May 2013 by collecting production data and catching efforts on squid by type of catch and fishing gear, the period of 2005-2010. Data obtained from the Department of Marine and Fisheries of South Sulawesi Province, Indonesia. Production data and catching efforts are standardized, then continued potential sustainability estimation analysis using the Schaefer and Fox Model. Data analysis was done by comparative descriptive. The results showed that squid in Pangkajene and Kepulauan waters based on Schaefer model approach was obtained by estimation of sustainable catch result 155.2326 tons per year, estimation of optimum catching effort (Fopt) 12,140.8780 trips per year. Based on Fox model approach shows the estimated value of sustainable catch is 131.6589 tons per year, estimation of optimum catching effort (Fopt) is 9,255.0821 trips per year. Based on this, the catching of squid in Pengkajene and Kepualaun waters has not experienced over fishing.Keywords: catch, MSY, Foptimum, FPI, effort standard.